PESANTREN TRANSFORMATION IN THE DIGITAL ERA: SOLUTION OR THREAT FOR ISLAMIC EDUCATION - Nisa, Durotun; Aimah, Siti; Fakhruddin, Fathiyah Mohd. (STAI Ma'had Aly Al-Hikam Malang, 2024)
This study aims to provide solutions for Islamic education in addressing the transformation of pesantren in the digital era by exploring collaborative approaches to building a balanced digital pesantren, where technology integration is carried out without sacrificing Islamic values. This research design uses a qualitative method with a case study approach. The source of informants of this research is the caregivers and students of Mabadiul Ihsan, which is to explore their role in supporting the transformation of pesantren in the digital era. Data collection techniques in this study were interviews, observations, and document studies to provide a comprehensive and in-depth understanding in the research of Pesantren Transformation in the Digital Age Solutions and Threats for Islamic Education. The data analysis technique in this study uses Miles and Huberman, this analysis process involves three main stages, namely data reduction, data presentation, and conclusion drawing or verification. digital technology allows the adoption of modern learning methods, such as blended learning and distance learning, thereby increasing access and effectiveness of education. However, this change also presents challenges in the form of reduced direct interaction and the need to strengthen character education to maintain the traditional values of pesantren. Keywords: Pesantren Transformation; Digital Era; Islamic Education; Digital Technology; Islamic Values. Abstrak Penelitian ini bertujuan untuk memberikan solusi bagi pendidikan Islam dalam menyikapi transformasi pesantren di era digital, dengan mengeksplorasi pendekatan kolaboratif untuk membangun pesantren digital yang berimbang, di mana integrasi teknologi dilakukan tanpa mengorbankan nilai-nilai Islam. Desain penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus. Sumber informan penelitian ini adalah pengasuh dan santri Mabadiul Ihsan, yaitu untuk mengeksplorasi peran mereka dalam mendukung transformasi pesantren di era digital. Teknik pengumpulan data dalam penelitian ini adalah wawancara, observasi, dan studi dokumen untuk memberikan pemahaman yang komprehensif dan mendalam dalam penelitian transformasi pesantren di era digital solusi dan ancaman bagi pendidikan Islam. Teknik analisis data dalam penelitian ini menggunakan Miles dan Huberman, proses analisis ini melibatkan tiga tahap utama, yaitu reduksi data, penyajian data, dan penarikan kesimpulan atau verifikasi. Teknologi digital memungkinkan diadopsinya metode pembelajaran modern, seperti blended learning dan distance learning, sehingga meningkatkan akses dan efektivitas pendidikan. Namun perubahan ini juga menghadirkan tantangan berupa berkurangnya interaksi langsung dan perlunya penguatan pendidikan karakter untuk mempertahankan nilai-nilai tradisional pesantren. Kata Kunci: Transformasi Pesantren; Era Digital; Pendidikan Islam; Teknologi Digital; Nilai-nilai Islam.